PENERAPAN METODE PEMBELAJARAN RESITASI DAN DISKUSI UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN EKONOMI POKOK BAHASAN PERPAJAKAN PADA KELAS XI IPS MA ABU DZARRIN KENDAL BOJONEGORO TAHUN AJARAN 2019/2020 - Aisyah, Siti Umi Nur; Sarjono, Sarjono; Hariyadi, Ahmad (LPPM STKIP PGRI Bandar Lampung, 2020)
The application of learning methods in terms of suitability and effectiveness of the characteristics of learning materials and students. This research is to understand: (1) the workings of applying learning and discussion methods that can improve student learning outcomes. (2) Learning Implementation Methods Learning Methods on Student Learning Outcomes. (3) Learning Implementation Methods Learning and Learning Methods for Student Learning Outcomes to Subjects of Economic Subjects of Taxation. Classroom Action Research with Qualitative approval. The population of this study were 38 students. Data collection using the Pre Test and Post Test methods in Cycle I and Cycle II. Pre Test scores are a reference to students' abilities before applying the learning and recitation learning methods, while the post test scores are used to reflect student learning outcomes after applying the recitation and discussion learning methods. KKM Economics subjects in Class XI IPS MA ABU DZARRIN Kendal Bojonegoro amounted to 75. Student assistance is considered Completed (T) if the test score is equal to or more than 75, suitable students Not Completed (TT) use test scores less than 75. Data analysis Obtained the results of research (1) Student pre-test scores before applying the learning and discussion methods very much that have not met the KKM of 52.6%. (2) The results of the improvement of learning cycle I by applying recitation and discussion methods only 60.5% of students who meet the KKM while 39.5% of students scored below the KKM. (3) The results of improving cycle II It is estimated that 92% of students have reached the KKM. Increasing student learning outcomes in the second cycle is very significant, then determined recitation learning methods and discussions can improve student learning outcomes.